Attraction and subsidy analysis of the 21st-Century Maritime Silk Road: A hub line location approach. (29th September 2022) - Zheng, Jianfeng; Hou, Lili; Wang, Yao; Mei, Rui
As a sea route corridor, the 21st Century Maritime Silk Road (TCMSR) has a potential impact on container routing between Asia and Europe. In this paper, all considered ports along this corridor are assumed to be hub ports. When transporting containers along the TCMSR, this paper considers the subsidy policy, represented by a subsidy factor. In order to explore the attraction and subsidy analysis of the TCMSR, a bilevel programming model is proposed. The upper level model aims to determine the optimal subsidy factor along the TCMSR, and the lower level model is formulated as a hub line location problem. By enumerating all different values of the subsidy factor, the bilevel programming model is reduced to the lower level model. Computational experiments show that, the attraction of the TCMSR mainly depends on the subsidy policies to be implemented along the TCMSR.